A Multifunctional Tyrosine‐Immobilized PAH Molecule as a Universal Cathode Interlayer Enables High‐Efficiency Inverted Polymer Solar Cells (Advanced Optical Materials 21/2021). Issue 21 (5th November 2021) - Kim, Young‐O; Moon, Byung Joon; Lee, Aram; Kim, Jin Il; Lee, Seoung‐Ki; Lee, Yoon‐Sik; Bae, Sukang; Hong, Byung Hee; Jung, Yong Chae
Abstract : Yong Chae Jung and co‐workers report Tyr–perylene diimide–Tyr (PDI‐Y) as a molecular‐based artificial photosystem II, see article number 2101006 . From spectroscopic and theoretical investgations, they reveal that the presence of covalently‐immobilized Tyr can enhance the intramolecular charge separation, leading to a significant reduction of the exciton recombination probability. Additionally, it is found that the utilization of PDI‐Y as a cathode interlayer can improve the photovoltaic performance of polymer solar cells owing to its light‐harvesting ability and charge generation/transport capability.